ANALYSIS: ALIGNING INFORMATION SYSTEMS AND BUSINESS PROCESSES IN THE COFFEE INDUSTRY - Khan, Mujeeb Ullah (Universitas Islam Negeri Raden Intan Lampung, 2024)
The coffee industry, which encompasses more than 25 million smallholder farmers worldwide, requires efficient and sustainable supply chain management. Integrating Information Systems (IS) with business processes in the coffee sector can enhance operational performance. This study utilizes a combination of literature reviews and field surveys to examine the alignment of IS in the industry. The primary findings underscore the significance of web-based and desktop solutions in facilitating stakeholder access to accurate information. Entity Relationship Diagrams (ERD) and Data Flow Diagrams (DFD) ensure a comprehensive understanding of the system's structure. The integration of IS supports sustainable practices by monitoring environmental impact and promoting fair trade. The discussion highlights the benefits of digital transformation, including improved decision-making and operational efficiency. Adopting structured approaches such as ERD and DFD facilitates effective communication among stakeholders. The integration of IS with sustainable practices reflects a commitment to environmental stewardship and ethical business conduct. Recommendations include the continued development of IS customized to meet the needs of stakeholders, fostering collaboration for innovation, enhancing digital literacy, designing sustainable IS solutions, and advocating for the adoption of IS policies. The implementation of these recommendations has the potential to drive efficiency, sustainability, and stakeholder engagement in the coffee industry.